The Relation between Love and Trust towards Married Couples in Makassar - Andi Nur Ismail Budiman; Asniar Khumas; Faradillah Faradillah (Jurnal Psikologi Karakter, 2023)
The love is an important component in any marital relationship. The love of married couples weakens due to various bad events that occur in marriage. The purpose of this study was to determine the relationship between love and trust in married couples in Makassar City. This research uses quantitative methods. The subjects in this study were 101 people who are husband or wife, and live in Makassar City. Data analysis used Spearman rho correlation analysis. The results of this study indicate that the significant value is p = 0.000 (p <0.05), and the value of the correlation coefficient is R = 0.763. Thus, there is a relationship between love and trust in married couples in Makassar City. This research contributes to the field of psychology, particularly family psychology, related to love and trust in married couples.